2023
DOI: 10.18388/abp.2020_6517
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin inhibits the expression of MYC and CYP2E1 and reduces oxidative stress in the myocardium of spontaneously hypertensive rats

Abstract: Oxidative stress is one of the most important pathological processes in chronic heart failure caused by hypertension. These processes involve MYC-regulated mechanisms, including the induction of CYP2E1 as a potent prooxidant factor. In this work, we used qPCR, Western blot analysis, and biochemical markers of oxidative stress to investigate the ability of quercetin to inhibit oxidative stress by modulating MYC expression. We studied spontaneously hypertensive rats (SHRs) in which the onset of cardiac pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A study demonstrated that quercetin significantly declines oxidative stress by reducing the expression of CYP2E1 resulting in diminish lipid peroxidation or free radical generation. [76] The other three compounds also showed favorable docking scores with CYP2E1. The regulation of hepatic CYP2E1's physiological expression is principally governed by the transcription factors hepatocyte nuclear factor-alpha (HNF-α) and NF-kB in the context of inflammatory conditions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A study demonstrated that quercetin significantly declines oxidative stress by reducing the expression of CYP2E1 resulting in diminish lipid peroxidation or free radical generation. [76] The other three compounds also showed favorable docking scores with CYP2E1. The regulation of hepatic CYP2E1's physiological expression is principally governed by the transcription factors hepatocyte nuclear factor-alpha (HNF-α) and NF-kB in the context of inflammatory conditions.…”
Section: Discussionmentioning
confidence: 92%
“…The protein‐ligand interaction image presented shows quercetin forms hydrogen bonds with three residues, Val388, Asn220, and Asp102, of CYP2E1 (Supplementary file). A study demonstrated that quercetin significantly declines oxidative stress by reducing the expression of CYP2E1 resulting in diminish lipid peroxidation or free radical generation [76] . The other three compounds also showed favorable docking scores with CYP2E1.…”
Section: Discussionmentioning
confidence: 99%
“…The myocardium of spontaneously hypertensive rats (SHRs) overexpresses MYC and its downstream target CYP2E1, whose overexpression leads to oxidative stress and other pathological processes. Long-term treatment with quercetin, a flavonoid with potential cardiovascular beneficial effects, resulted in a significant reduction of blood pressure with concomitant downregulation of MYC and CYP2E1, significantly improving the prooxidant-antioxidant profile ( Maksymchuk et al, 2023 ). Whether downregulation of MYC alone would reduce blood pressure, CYP2E1 expression, and curb the oxidative stress, still remains to be seen.…”
Section: Myc’s Involvement In Diseases and Conditionsmentioning
confidence: 99%
“…In the case of high-density microsomes obtained from rats exposed to ethanol, a reduced GSH/GSSG ratio of 2.9:1 was observed, indicating an elevated level of oxidative stress following ethanol consumption [162]. The increased oxidative stress was associated with the up-regulated expression of CYP2E1, as demonstrated by the presence of 4-hydroxynonenal (4-HNE) protein adducts in adipocytes and an elevation in ADIPO carbonylation [163][164][165][166]. While overexpression of CYP2E1 in 3T3-L1 adipocytes did not affect intracellular ADIPO concentration [161], ethanol culture did lead to the inhibition of ADIPO release into the extracellular medium.…”
Section: Adipomentioning
confidence: 99%